Whip black corals (Antipatharia: Antipathidae: Stichopathes) of the Mesophotic Coral Ecosystem of Mo’orea (French Polynesia), with the description of a new species - Terrana, L.; Rouzé, H.; Opresko, D.m.; Consortium, Under The Pole; Eeckhaut, I.; Dubois, P.; Hédouin, L.; Godefroid, M. (Zootaxa, 2024)
Black corals are key species of marine ecosystems. They can be found in dense aggregations worldwide, but some parts of the world remain totally unexplored. This is the case of the Mesophotic Coral Ecosystem of Mo’orea where the Under the Pole scientific expedition explored mesophotic ecosystems between 60 and 120 m depth and focused on whip black corals. A total of 64 specimens were analyzed morphologically and genetically, and all belonged to the genus Stichopathes. Among them, we describe the new species Stichopathes desaturata sp. nov. It is characterized by an unbranched corallum, irregularly sinuous, with a basal diameter not exceeding 1 mm, reaching a dozen of cm in height. The polyps measure 0.50–1.0 mm in transverse diameter, the interpolypar space is well defined and up to 0.50 mm, with 6–8 polyps per cm. The polypar spines are taller than abpolypar spines, reaching 0.13 mm, perpendicular to the corallum, and conical with a pointed tip, with round and/or elongated papillae on two thirds of the spine. The abpolypar spines are conical to triangular, inclined upwards, with the same ornamentation as the polypar spines. We also identified specimens assigned as Stichopathes cf. contorta and four other putative species. Genetic analyses showed that Mo’orea specimens grouped in three different clades. Analyses of endosymbionts showed that the association with Symbiodiniaceae was likely not involved in the process of host species delineation.